2022
DOI: 10.1371/journal.ppat.1010332
|View full text |Cite
|
Sign up to set email alerts
|

Maf/ham1-like pyrophosphatases of non-canonical nucleotides are host-specific partners of viral RNA-dependent RNA polymerases

Abstract: Cassava brown streak disease (CBSD), dubbed the “Ebola of plants”, is a serious threat to food security in Africa caused by two viruses of the family Potyviridae: cassava brown streak virus (CBSV) and Ugandan (U)CBSV. Intriguingly, U/CBSV, along with another member of this family and one secoviridae, are the only known RNA viruses encoding a protein of the Maf/ham1-like family, a group of widespread pyrophosphatase of non-canonical nucleotides (ITPase) expressed by all living organisms. Despite the socio-econo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…ITPase in Ugandan cassava brown streak virus (UCBSV) is required for its infectivity of cassava, which contain high levels of noncanonical nucleotides. A fraction of UCBSV‐ITPase is covalently associated with the viral RNA polymerase NIb, consistent with its functioning to prevent misincorporation of noncanonical nucleotides during viral replication (Valli et al, 2022).…”
Section: Itpase Deficiency and Clinically Relevant Variants In Itpamentioning
confidence: 78%
“…ITPase in Ugandan cassava brown streak virus (UCBSV) is required for its infectivity of cassava, which contain high levels of noncanonical nucleotides. A fraction of UCBSV‐ITPase is covalently associated with the viral RNA polymerase NIb, consistent with its functioning to prevent misincorporation of noncanonical nucleotides during viral replication (Valli et al, 2022).…”
Section: Itpase Deficiency and Clinically Relevant Variants In Itpamentioning
confidence: 78%
“…This fusion may ensure that an active ITPase dimer co-localizes with and protect the viral replicase. The production of both forms of ITPase is due to a weak proteolytic cleavage caused by a T in the last position of the cleavage site VDTQ/T, which is sub-optimally recognized by the protease Nla-Pro (Valli et al, 2022). Interestingly, a T is found at a similar position on the putative cleavage site preceding the MMV ITPase (Fig.…”
Section: Phytoviral Itpase Function and Originsmentioning
confidence: 94%
“…CsTLV is an atypical member of the Secoviridae, containing a Maf/Ham1 domain located in RNA1 downstream of the RdRp domain (Leiva et al, 2022). Maf/HAM1 proteins are nucleoside triphosphate (NTP) pyrophosphatases that protect cells by hydrolyzing non-canonical NTPs, preventing their incorporation into DNA or RNA (Noskov et al, 1996;Mbanzibwa et al, 2009;Tomlinson et al, 2019;Valli et al, 2022). Recent results demonstrated that Maf/Ham1 domain is associated with the development of necrosis in N. benthamiana plants (Tomlinson et al, 2019) and Valli et al (2022) suggests that the HAM1 domain participates in viral replication because it might be covalently bound during CBSV and EuRV infections.…”
Section: Considerations Of Cstlv As An Atypical Member Of the Secovir...mentioning
confidence: 99%